The use of magnetoencephalographic brainwaves in detecting neurocognitive impairments in traumatic brain injury - Yik, Neoh Yee (2018)
Objectives: The purpose of this study was to investigate the potential of magnetoencephalography (MEG) as a tool for early detection of brainwave disruption in traumatic brain injury (TBI) patients and compare the MEG results to neuropsychological assessments. Methods: Our study consisted of 12 TBI patients aged 14–26 who had a Glasgow Coma Scale (GCS) of 9–13 in the first 24 hours after a motor vehicle accident. According to the severity of their GCS score, and regardless of the type of brain injury, patients were then distributed into two groups, moderate TBI (GCS score 9–12) or mild TBI (GCS score of 13). Neuropsychological tests were given to patients before the MEG recording. MEG was used to measure the power of the different frequency bands delta, theta, alpha, beta, and gamma. Results: The power of the beta frequency band was reduced and the theta/beta ratio was significantly increased in the moderate TBI group compared to the mild TBI group. Neuropsychological assessments results tended to support this finding but did not reach significance. Discussion: The MEG results suggest that moderate TBI patients have greater processing and attention deficits than mild TBI patients. We concluded that MEG plays an important role in objectively detecting brain wave changes after TBI, which has implications for the prediction of cognitive sequelae after TBI.